The Influence of Financial Technology on Environmental Performance: The Mediating Role of Green Knowledge Management - Aurora Nanda Avprita; Muhammad Ali Fikri (Transpublika Publisher, 2026)
The digital era has brought about technological advance, one of which is in the financial sector namely financial technology, which is designed to facilitate human activities, particularly in financial management. This facilitates access to the banking world, both internally and externally, the existence of this technology has had a number of extraordinary positive impacts, making environmental performance more organized and able to balance the role of the environmental performance as a supporter of financial technology. The purpose of this study is to determine the extent of the influence of financial technology on environmental performance mediated by green knowledge management at Bank Pembangunan Daerah Yogyakarta (BPD DIY). The research subjects were 100 employees of the Bank Pembangunan Daerah Yogyakarta main office. Sampling in the study used probability sampling, which means that all employees had the opportunity to participate in this study. The data collection method used a questionnaire, and the data analysis tool used Smart PLS 4.0 software. This results of the instrument scale test used were validity and reliability tests. Hypothesis testing showed that financial technology has a positive effect on environmental performance, financial technology has a positive effect on green knowledge management, green knowledge management has a positive effect on environmental performance, and green knowledge management mediates the positive effect of financial technology on environmental performance.